Validation of the Childhood Dysphagia Management Scale (CDMS): An Impact Scale for determining medical home for dysphagia. (June 2021) - Maybee, Jennifer; Jackson, Arwen; Wolter-Warmerdam, Kristine; Hickey, Francis; Prager, Jeremy; DeBoer, Emily
Abstract: Background: The results and recommendations from instrumental assessments of swallowing do not, by themselves, provide guidance regarding the type of medical management that might be needed for the pediatric patient with dysphagia. The aim of this study is to evaluate the reliability and validity of the Childhood Dysphagia Management Scale (CDMS), a clinical scale developed to estimate the impact of dysphagia and determine the need for a multidisciplinary medical home to manage dysphagia. Methods: This was a prospective observational study implemented in three phases to evaluate validity and reliability of the CDMS. Analyses for internal consistency, inter-rater and intra-rater reliability, repeated measure, content, structural, criterion and external validity and hypothesis testing were conducted. Results: This study established content, structural, internal, external, and criterion validity of the CDMS. The CDMS was found to have robust inter-rater (κ = 0.776) and intra-rater reliability (κ = 0.853), and consistency across repeated measures (κ = 0.853). Providers who used the CDMS had a high level of agreement with the recommended medical management plan. CDMS scores correlated (F(5, 118) = 22.105, p < 0.001) with Functional Oral Intake Scale (FOIS) scores confirming that patients with significant diet restrictions were more likely to be referred for multidisciplinary care. To establish external validity, the CDMS was administered to a higher risk group, patients with Down syndrome, who were more likely to be referred for multidisciplinary care based on CDMS results versus the general swallowing disorders clinic population (F(1, 281) = 24.357, p < 0.001). Conclusion: The CDMS is a reliable and valid scale for guiding decision-making regarding the medical home for pediatric dysphagia management.